Effectiveness of Combination Myofascial Release and Kinesio Taping Intervention on Range of Motion Improvement in Elderly with Knee Osteoarthritis - Afif Zainuri Wafiq; Atika Yulianti (Universitas Udayana dan Diaspora Taipei Medical University, 2020)
Introduction: Knee Osteoarthritis is a condition that frequently occurs in elderly which has a major impact on the elderly’s disability. As a degenerative disease, knee osteoarthritis occurs due to cartilage damage which is then accompanied by inflammation, pain, stiff joints and muscles thereby limiting the range of motion. This research aims to compare the effect of Kinesio taping and a combination of myofascial release and Kinesio taping intervention on ROM improvement in elderly with knee osteoarthritis.Methods: This study applies a quasi-experimental design with a non-equivalent group approach. Goniometer is applied as a measurement instrument. 25 people participated in this study who were recruited through purposive sampling. The sample was then divided into 2 groups which were given treatment 3 times a week in one month. The control group with Kinesio Taping treatment consisted of 14 samples and the case group with a combination treatment of myofacial release and Kinesio taping consisted of 11 samples. Furthermore, data analysis was performed with the Shapiro Wilk test, Wilcoxon rank test, and the Mann-Whitney test using SPSS version 25.Results: The comparison test results show that the significance value of p yields 0.6> 0.05, therefore H1 is rejected, and H0 is accepted. The interpretation of these results is that there is no significant difference between the effects of Kinesio taping and the combination of myofacial release and Kinesio taping on increasing ROM in the elderly with the risk of knee osteoarthritis.Conclusion: This study shows that there is no significant difference in the effect of the treatment of Kinesio taping and the combination of myofacial release and Kinesio taping in increasing ROM in the elderly with osteoarthritis.